Financial Statement Analysis to Assess Financial Performance at the Fish Quarantine Center, Jakarta II Ministry of Maritime Affairs and Fisheries, Quality Control, and Product Safety - Ratnayulis, Wita; Madiistriyatno, Harries; Naldi Sahim, Aswin (Universitas Ibn Khladun Bogor, 2024)
With regard to efficacy, efficiency, and growth, the objective of this research is to assess the financial standing of the Ministry of Marine Affairs and Fisheries' Jakarta II Fish Quarantine and Inspection Agency for the years 2021–2023. Financial Statements for the years 2021–2023 are the data used in this analysis. Documentation and literature review are the methods utilized to obtain data. This study employed descriptive qualitative data analysis using growth ratios, effectiveness, and efficiency. The findings demonstrated that the Jakarta II Fish Quarantine and Inspection Agency, Center had generally demonstrated strong financial management. This may be observed from the effectiveness ratio calculation results, which are classified as effective because the average effectiveness is over 100%, or 113.51%, and as less efficient because the average efficiency is below 100%, or 62.65%. With a negative number, the growth ratio falls into the bad group.